Islamic Cyber Youth: Qur'an On Social Media - Qithrotun Nida Aulia; Sholahuddin Al Ayubi (Jurnal Semiotika Quran, 2023)
In this digital era, social media has become an effective communication tool to make it easier for the public to find information and also as a tool to convey ideas and educate the younger generation. By utilizing the role of social media to educate the public about understanding the principles of the Qur'an. This article aims to explore the role of Islamic Cyber Youth in the publication of the Al-Quran through social media. With the development of information technology and the use of social media platforms as a means to share the understanding of Al-Quran verses, and interpretations, to the younger generation. Through content analysis and literature search, this study describes how Islamic Cyber Youth uses social media to present and disseminate the Koran to a wider audience, both within the Muslim community and among non-Muslims. The results of this study indicate that Islamic Cyber Youth often publishes quotes, and personal views on Al-Quran verses on social media sites such as Instagram, Twitter, and YouTube. They actively discussed, commented, and exchanged ideas and personal experiences about the Qur'an which affects everyday life. Islamic Cyber Youth acts as an advocate and educational media as well as interpreter of Islamic principles contained in the Al-Quran into a context and language that is more relatable and easily understood by the younger generation.